2020
DOI: 10.3389/fnins.2020.00197
|View full text |Cite
|
Sign up to set email alerts
|

Mental Rotation of Digitally-Rendered Haptic Objects by the Visually-Impaired

Abstract: In the event of visual impairment or blindness, information from other intact senses can be used as substitutes to retrain (and in extremis replace) visual functions. Abilities including reading, mental representation of objects and spatial navigation can be performed using tactile information. Current technologies can convey a restricted library of stimuli, either because they depend on real objects or renderings with low resolution layouts. Digital haptic technologies can overcome such limitations. The appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…coauthors [29] observed that high visuospatial imagers better recognized raised-line drawings than low visuospatial imagers. Similarly, Kalisch et al [24] found better haptic recognition of solid objects in aged persons with high cognitive abilities compared to their less-skilled peers. The fact that a visual mental rotation test positively correlated with the performance in a haptic task is also consistent with a wide literature highlighting the role of a common multimodal representation system processing both visual and haptic information [39]- [47].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…coauthors [29] observed that high visuospatial imagers better recognized raised-line drawings than low visuospatial imagers. Similarly, Kalisch et al [24] found better haptic recognition of solid objects in aged persons with high cognitive abilities compared to their less-skilled peers. The fact that a visual mental rotation test positively correlated with the performance in a haptic task is also consistent with a wide literature highlighting the role of a common multimodal representation system processing both visual and haptic information [39]- [47].…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies focused on how haptic perception can be exploited to generate, manipulate and improve mental representations of spatial information. For instance, Tivadar and coauthors [23], [24] used a haptic tablet to present letters at different orientations to blindfolded sighted or blind persons that were asked to indicate if the letter was either in a normal or mirror-reversed form. Results showed higher performance for normal letters compared to mirrored letters and for trained as compared to untrained letters, thereby demonstrating mental rotation of haptic letter stimuli.…”
Section: B Haptic Perception and Spatial Skillsmentioning
confidence: 99%
“…More extensive training would likely improve performance on the tablet task under haptic-only conditions. In fact, previous results show that after a training session of about 45 minutes on the haptic tablet, blindfolded sighted participants as well as visually impaired individuals were able to discriminate letters and to build mental representations of these letters that they then mentally manipulated in a mental rotation task 32,33 .…”
Section: Discussionmentioning
confidence: 97%
“…This type of haptic tablet uses ultrasonic vibrations to modulate the friction of a at screen under the actively exploring nger, and thus simulates the localized perception of texture 30,31 . Such devices are proving to be especially effective as sensory substitution devices for the visually-impaired, given their ability to simulate the perception of objects and their very low training requirements 32,33 . What is distinct about these technical innovations is their ability to render recognisable and manipulable textures and objects, rather than simply provide localized haptic feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Mental rotation of objects has been linked to motor experience, hormones, and experience-dependent processes 36 38 . Previous studies showed that blind individuals, even those who acquired blindness at birth and thus have no visual experience, are able to mentally rotate objects perceived through touch and are not deficient in their mental rotation abilities compared to sighted adults performing the same task also through touch 39 – 41 . Overall, the current results strengthen previous findings concluding that both the construction of a mental image and its rotation are not limited to information acquired via the visual modality.…”
Section: Discussionmentioning
confidence: 99%